Characterization of CO2 laser browning of dough. (March 2019) - Blutinger, Jonathan David; Meijers, Yorán; Chen, Peter Yichen; Zheng, Changxi; Grinspun, Eitan; Lipson, Hod
Abstract: We study the application of laser-heating technology to browning dough, due to its potential for high-resolution spatial and surface color control. An important component of this process is the identification of how laser parameters affect browning and baking and whether desirable results can be achieved. In this study, we analyze the performance of a carbon dioxide (CO2 ) mid-infrared laser (operating at 10.6 μm wavelength) during the browning of dough. Dough samples—consisting of flour and water—were exposed to the infrared laser at different laser power, beam diameter, and sample exposure time. At a laser energy flux of 0.32 MW m −2 (beam diameter of 5.7 mm) and sample exposure time of 180 s we observe a maximum thermal penetration of 0.77 mm and satisfactory dough browning. These results suggest that a CO2 laser is ideal for browning thin goods as well as for food layered manufacture. Industrial relevance: A CO2 laser that operates at a wavelength of 10.6 μm (IR) was used as an alternative method for browning dough. The high-power flux of the laser and the high energy absorption of food at this wavelength allow for rapid surface browning; however, the high absorption limits thermal penetration depth. Nevertheless, accuracy of the laser beam enables high resolution spatial and thermal control of the non-enzymatic browning process. This high precision cooking makes laser-browning particularly ideal for food layered manufacture (FLM), a food processing technique that has gained increased attention in recent years. Using FLM, one can adjust the printed layer height to match cooking penetration depth. As a digital manufacturing technology, laser-browning could also enable manufacture of highly complex and customized food geometries and textures. Highlights: A CO2 infrared laser can achieve controlled surface browning of dough products. Dough browning can be achieved at 0.32 MW m −2 laser flux and 180 s exposure time. High exposure time and low beam flux results in baking penetration up to 0.77 mm. This processing technique is particularly useful for food layered manufacture.